Natural killer T (NKT) cells accelerate Shiga toxin type 2 (Stx2) pathology in mice - Obata, Fumiko; Subrahmanyam, Priyanka B.; Vozenilek, Aimee E.; Hippler, Lauren M.; Jeffers, Tynae; Tongsuk, Methinee; Tiper, Irina; Saha, Progyaparamita; Jandhyala, Dakshina M.; Kolling, Glynis L.; Latinovic, Olga; Webb, Tonya J. (Frontiers in Microbiology, 2015)
Shiga toxin-producing Escherichia coli (STEC) is a leading cause of childhood renal disease He-molytic Uremic Syndrome (HUS). The involvement of renal cytokines and chemokines is sus-pected to play a critical role in disease progression. In current article, we tested the hypothesis that NKT cells are involved in Stx2-induced pathology in vivo. To address this hypothesis we compared Stx2 toxicity in WT and CD1 knockout (KO) mice. In CD1KO mice, which lack nat-ural killer T (NKT) cells, Stx2-induced pathologies such as weight loss, renal failure, and death were delayed. In WT mice, Stx2-specific selective increase in urinary albumin occurs in later time points, and this was also delayed in NKT cell deficient mice. NKT cell-associated cytokines such as IL-2, IL-4, IFN-γ and IL-17 were detected in kidney lysates of Stx2-injected WT mice with the peak around 36 h after Stx2 injection. In CD1KO, there was a delay in the kinetics, and increases in these cytokines were observed 60 h post Stx2 injection. These data suggest that NKT cells accelerate Stx2-induced pathology in mouse kidneys. To determine the mechanism by which NKT cells promote Stx2-associated disease, in vitro studies were performed using murine renal cells. We found that murine glomerular endothelial cells and podocytes express functional CD1d molecules and can present exogenous antigen to NKT cells. Moreover, we observed the direct interaction between Stx2 and the receptor Gb3 on the surface of mouse renal cells by 3D STORM-TIRF which provides single molecule imaging. Collectively, these data suggest that Stx2 binds to Gb3 on renal cells and leads to aberrant CD1d-mediated NKT cell activation. Therefore, strategies targeting NKT cells could have a significant impact on Stx2-associated renal pathology in STEC disease.